New Quality Productive Forces in Taiwan Evidence from the Three New Economy Framework - Ling-Chih Chen; Yung-Shan Su; Wen-Tha Hsu; Tai-San Hu; Chiang Kao (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
This study aims to measure the development of New Quality Productive Forces (NQPF) in Taiwan and explain their regional growth patterns, disparities, and spatial coordination dynamics under the Three New Economy framework. The study analyzes 19 Taiwanese administrative units from 2016 to 2022 using the super-efficiency MinDW Malmquist index, Dagum Gini decomposition, spatial conditional kernel density estimation, and spatial Markov chain analysis. Taiwan’s NQPF increased moderately, with a national average index of 1.02, but growth remained uneven. Six regional growth patterns were identified, ranging from synchronous growth in major innovation corridors to incubation patterns in structurally constrained areas. Regional inequality widened after 2019 and formed a North high, East low spatial gradient, with between-region disparity contributing the largest share of total inequality. Spatial analysis further shows that backwash effects constrain low-tier regions, whereas medium-high regions such as Taichung and Kaohsiung function as potential spread transmitters. This study extends NQPF literature by operationalizing the Three New Economy concept within an efficiency-based productivity framework and by integrating productivity, inequality, and spatial mobility analysis in a single empirical design. The findings suggest the need for innovation corridors, relay-region strengthening, and location-specific transformation strategies. The study is limited to available regional data for 2016–2022; future research should incorporate firm-level data and longer post-pandemic observations to refine causal interpretation.